Eksplorasi Makna Laba dengan Pendekatan Etnografi - Mursy, Austina Luckyta; Triyunono, Iwan; Rosidi (Universitas Brawijaya, Indonesia, 2014)
The study aims to reveal the meaning of profit and understand the concept of profit, and the distribution of profit according to the customs, traditions, and cultures at Aisyiyah hospitals. This study uses qualitative research with ethnographic approach. This study tries to reveal the meaning of profit through customs, traditions, and rituals that has been practiced in the hospital. This study found that; first, profit is interpreted based on the physical appearance in the form of material or money. Second, the form of material profit used as a tool in order to pay for liability payment of the hospital to the external dispute. Third, material profit has a role as a tool in order to improve the welfare of employees. Fourth, the goal of material profit is using for the development of hospitals and funding a dakwah (missionary endeavour) of Muhammadiyah organization.